Boundaries, Privacy, and Social Media Use in Higher Education: What do Students Think, Want, and Do? - Dennen, Vanessa P.; Burner, Kerry J. (AoIR Selected Papers of Internet Research, 2013)
In this study, we examine university students’ beliefs and behaviors related to social media, identity, and boundaries in a higher education context. Findings suggest a complex and at times contradictory relationship between students and social media, in which they enjoy free access to information about and contributed by other people and freely share about themselves in a social or personal context, but are reticent to be active contributors in an academic context. Although students seek information about their instructors online, they do not believe that instructors might reciprocate. In contrast to a common assumption, they do not want to use social media in their coursework and prefer to restrict both their communication with instructors and coursework to private tools and settings.